Pengaruh Kualitas Layanan Dan Diskon Terhadap Kepuasan Pelanggan Maxim Di Kota Medan - Ginting, Maretta; Eva Solita Pasaribu; Ronnie Togar Mulia Sirait (Universitas Sari Mutiara Indonesia, 2024)
This research aims to determine and analyze the influence of service quality and discounts partially on customer satisfaction as well as the influence of service quality and discounts simultaneously on customer satisfaction. The research method used is quantitative descriptive. The population in this study were Maxim customers in Medan City. The sample in this study consisted of 96 respondents using the Purpisive Sampling technique. The measurement scale used is the Likert Scale. Data collection techniques are carried out through observation, questionnaires and documentation. The data analysis techniques used are Instrument Test, Classic Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test and Determination Efficiency Test. The research results show that service quality has a partial effect on customer satisfaction, dikson has a partial effect on customer satisfaction and service quality and discounts have a simultaneous effect on customer satisfaction.